Visual Recovery after Penetrating Injury Through the Orbit - Kukuh Prasetyo; Angga Kartiwa (Majalah Oftalmologi Indonesia, 2016)
Background: Penetrating trauma through the orbit cavity by blunt edged instrument could bring destructionto many organs located in it. This article is aimed to report a case of severe penetrating injury throughthe orbit cavity with a good visual recovery after surgical treatment.Case Illustration: A 29-year-old male came to Cicendo National Eye Hospital with a complaint ofbloody eye. His head was hit by fallen wall from behind while he was working using crowbar thatcaused the tip of crowbar penetrated into intracranial cavity through the right orbit cavity. Vital signswere within normal limit, with the crowbar fixated on 2 mm below the margin of inferior orbital edge.Visual acuity was 2/60 (bed side examination) without any RAPD. CT-scan showed the tip of crowbarentered cranial cavity. Patient was diagnosed with penetrating injury through the orbit and referred toNeurosurgery Department. Operation was done under general anesthesia and it was found that the tipripped of duramater on frontal region and both inferior rectus and inferior oblique muscle were rippedoff. We decided to leave the eye and give methyl prednisolone iv 1 g a day. Post operative examinationshowed that the visual acuity was 20/60 and patient was unable to move the right eye downward.Patient did not complain of double vision on primary position.Conclusion: Penetrating injury could be devastating for many organs inside the orbit. With a carefulexamination and correct management, vision can be saved.Keywords: penetrating injury, orbital cavityBackground: Penetrating trauma through the orbit cavity by blunt edged instrument could bring destructionto many organs located in it. This article is aimed to report a case of severe penetrating injury throughthe orbit cavity with a good visual recovery after surgical treatment.Case Illustration: A 29-year-old male came to Cicendo National Eye Hospital with a complaint ofbloody eye. His head was hit by fallen wall from behind while he was working using crowbar thatcaused the tip of crowbar penetrated into intracranial cavity through the right orbit cavity. Vital signswere within normal limit, with the crowbar fixated on 2 mm below the margin of inferior orbital edge.Visual acuity was 2/60 (bed side examination) without any RAPD. CT-scan showed the tip of crowbarentered cranial cavity. Patient was diagnosed with penetrating injury through the orbit and referred toNeurosurgery Department. Operation was done under general anesthesia and it was found that the tipripped of duramater on frontal region and both inferior rectus and inferior oblique muscle were rippedoff. We decided to leave the eye and give methyl prednisolone iv 1 g a day. Post operative examinationshowed that the visual acuity was 20/60 and patient was unable to move the right eye downward.Patient did not complain of double vision on primary position.Conclusion: Penetrating injury could be devastating for many organs inside the orbit. With a carefulexamination and correct management, vision can be saved.Keywords: penetrating injury, orbital cavityrauma pada wajah merupakan masalahsosial serta masalah kesehatanmasyarakat disebabkan karena frekuensiserta besaran masalah yang ditimbulkan, sertaketerkaitan dengan kecelakaan lalu lintas,tindak kejahatan, serta kaitannya denganrasa tidak aman. Bola mata meski hanyameliputi 0,27% dari seluruh permukaan tubuh,dan merupakan 4% dari seluruh permukaanwajah, mata merupakan bagian tubuh ketigayang paling terekspose oleh trauma.1,2 Kehilanganpenglihatan pada satu atau keduamata merupakan